Xeroderma Pigmentosum - A Family - Garg Anush; Singhi M.K (Wolters Kluwer Medknow Publications, 2000)
A family of xeroderma pigmentosum is reported. Four children of different ages were afflicted with varying clinical presentation. Sequential development and progression of the disease from freckling to malignancy within the family are discussed.